Comparative effects of human-equivalent low, moderate, and high dose oral prednisone intake on autoimmunity and glucocorticoid-related toxicity in a murine model of environmental-triggered lupus - Heine, Lauren K.; Benninghoff, Abby D.; Ross, Elizabeth A.; Rajasinghe, Lichchavi D.; Wagner, James G.; Lewandowski, Ryan P.; Richardson, Alexa L.; Li, Quan-Zhen; Buchweitz, John P.; Zyskowski, Justin; Tindle, Ashleigh N.; Skedel, Anna E.; et al. (Frontiers in Immunology, 2022)
Autoimmune diseases can be triggered by environmental toxicants such as crystalline silica dust (cSiO2). Here, we characterized the dose-dependent immunomodulation and toxicity of the glucocorticoid (GC) prednisone in a preclinical model that emulates onset and progression of cSiO2-triggered lupus. Two cohorts of 6-wk-old female NZBWF1 mice were fed either control AIN-93G diet or one of three AIN-93G diets containing prednisone at 5, 15, or 50 mg/kg diet which span human equivalent oral doses (HED) currently considered to be low (PL; 5 mg/d HED), moderate (PM; 14 mg/d HED), or high (PH; 46 mg/d HED), respectively. At 8 wk of age, mice were intranasally instilled with either saline vehicle or 1 mg cSiO2 once weekly for 4 wk. The experimental plan was to 1) terminate one cohort of mice (n=8/group) 14 wk after the last cSiO2 instillation for pathology and autoimmunity assessment and 2) to maintain a second cohort (n=9/group) to monitor glomerulonephritis development and survival. Mean blood concentrations of prednisone’s principal active metabolite, prednisolone, in mice fed PL, PM, and PH diets were 27, 105, 151 ng/ml, respectively, which are consistent with levels observed in human blood ≤ 12 h after single bolus treatments with equivalent prednisone doses. Results from the first cohort revealed that consumption of PM but not PL diet significantly reduced cSiO2-induced pulmonary ectopic lymphoid structure formation, nuclear-specific AAb production, and inflammation/autoimmune gene expression in the lung, splenomegaly, and glomerulonephritis in the kidney. Relative to GC-associated toxicity, PM but not PL diet elicited muscle wasting, but these diets did not affect bone density or cause glucosuria. Importantly, neither PM nor PL diet improved latency of cSiO2-accelerated death. PH-fed mice in both cohorts displayed robust GC-associated toxicity including body weight loss, reduced muscle mass, and extensive glucosuria 7 wk after the final cSiO2 instillation requiring their early removal from the study. Taken together, our results demonstrate that while moderate doses of prednisone can reduce important pathological endpoints of cSiO2-induced autoimmunity in lupus-prone mice such as upstream ectopic lymphoid structure formation, these ameliorative effects come with unwanted GC toxicity and, crucially, none of these three doses extended survival time.